2019
DOI: 10.21315/mjms2019.26.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Combatting Pseudoscience: A Science and Health Literacy Workshop to Improve Scientific Literacy in 16-Year-Old Students in Malaysia

Abstract: The rise of dubious medical practice and anti-vaccination groups in Malaysia suggests that the public needs to be equipped with the scientific literacy skills to navigate the healthcare landscape. Additionally, the overall result of the Programme for International Student Assessment (PISA) 2009+ for Malaysia suggests that the national scientific literacy levels of 16-year-old Malaysian students to be below the international and the Organisation for Economic Co-operation and Development (OECD) average. Conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
1
1
Order By: Relevance
“…Also, Bazaz et al's 17 in an investigation on on the health of cervical cancer in women of reproductive age using a tool in the framework of the HELIA tool, suggested that 42.7% of the individuals had limited health literacy. Although Ansari et al 18 that used the HELIA tool on the young population of 18−30 years old revealed that 82.9% of the individuals had sufficient health literacy, the reason for this difference could be the participants with suitable socioeconomic status (high school education or above and living in an affluent area in Tehran), while in the present study, a lower proportion (30.7%) of couples had more than a high school diploma or university education.…”
Section: Discussioncontrasting
confidence: 78%
“…Also, Bazaz et al's 17 in an investigation on on the health of cervical cancer in women of reproductive age using a tool in the framework of the HELIA tool, suggested that 42.7% of the individuals had limited health literacy. Although Ansari et al 18 that used the HELIA tool on the young population of 18−30 years old revealed that 82.9% of the individuals had sufficient health literacy, the reason for this difference could be the participants with suitable socioeconomic status (high school education or above and living in an affluent area in Tehran), while in the present study, a lower proportion (30.7%) of couples had more than a high school diploma or university education.…”
Section: Discussioncontrasting
confidence: 78%
“…21,22 Certainty, through a proper education initiative, science education can substantiate the enhancement of health literacy among a different category of groups including non-science. 23 Therefore, the more exposed they are to health education, the more literate they can be on health-related issues. 24,25 Gender was found to have a significant association with OHL showing that female has higher OHL than male.…”
Section: Discussionmentioning
confidence: 99%